Characterizing the social-ecological system for inland freshwater salinization using fuzzy cognitive maps: implications for collective management - Megan A Rippy; Benjamin H Roston; Emily Z Berglund; Payam Aminpour; Lauren Krauss; Shantanu V Bhide; Todd Schenk; Kristin Rowles; Shalini Misra; Thomas A Birkland; Sujay S. Kaushal; Stanley B Grant (Ecology and Society)
Current regulatory tools are not well suited to address freshwater salinization in urban areas, and the conditions under which bottom-up management is likely to emerge remain unclear. We hypothesize that Elinor Ostrom’s social-ecological systems (SESs) framework can be used to explore how current understanding of salinization might foster or impede its collective management. We focus on the Occoquan Reservoir, a critical urban water supply in Northern Virginia, USA, and use fuzzy cognitive maps (FCMs) to characterize stakeholder understanding of the SES that underpins salinization in the region. Hierarchical clustering of FCMs reveals four stakeholder groups with distinct views on the causes and consequences of salinization, and actions that could be taken to mitigate salinization, including technological, policy, and governance interventions and innovations. Similarities and differences across these four groups, and their degree of concordance with measured or modeled SES components, point to actions that could be taken to catalyze collective management of salinization in the region.